Clinical and radiological spectrum of cleidocranial dysplasia: A rare case report - Sneha H Choudhary; Lata M Kale; Sunil S Mishra; Nilofar S Zaidi (Wolters Kluwer Medknow Publications, 2017)
Cleidocranial dysplasia (CCD) is a rare congenital disorder which affects the bones and teeth. CCD usually has an autosomal dominant inheritance pattern, however, it may appear spontaneously in some cases. The most common features seen in CCD are aplastic or hypoplastic clavicles, late closure of fontanelle, open skull sutures, delayed exfoliation of deciduous teeth, delayed or failed eruption of permanent teeth, and supernumerary teeth. Here, we report a case of CCD in a 17-year-old female without any family history who presented with the complaint of missing teeth.